2009
DOI: 10.1590/s0104-07072009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos de biossegurança relacionados ao uso do jaleco pelos profissionais de saúde: uma revisão da literatura

Abstract: RESUMO:O estudo objetivou analisar a literatura publicada a respeito dos aspectos da biossegurança relacionados ao uso do jaleco pelos profissionais da saúde. Trata-se de uma revisão narrativa da literatura publicada no período de 1991 a 2008. Utilizou-se as bases de dados MEDLINE, LILACS e SciELO, sendo selecionados 22 artigos que foram agrupados para análise considerando os enfoques priorizados em: infecções cruzadas causadas por jalecos; jalecos contaminados; flora bacteriana em jalecos dos profissionais de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
0
6
0
26
Order By: Relevance
“…Quanto ao perfil de sensibilidade, foi constatado Staphylococcus aureus meticilina resistente, seguidos dos gram negativos resistentes aos antimicrobianos. Sendo assim, são potenciais veículos para a transmissão de microrganismos podendo ser considerado como fonte de infecções associadas aos cuidadores de saúde e de disseminação de patógenos multirresistentes (14)(15) . O descarte e/ ou a limpeza adequada dessas vestimentas envolvem questões, no mínimo, de higiene básica dos trabalhadores ou de preocupação com a transmissão por contato, até que sejam lavados.…”
Section: Resultados E Discussão Dos Dadosunclassified
“…Quanto ao perfil de sensibilidade, foi constatado Staphylococcus aureus meticilina resistente, seguidos dos gram negativos resistentes aos antimicrobianos. Sendo assim, são potenciais veículos para a transmissão de microrganismos podendo ser considerado como fonte de infecções associadas aos cuidadores de saúde e de disseminação de patógenos multirresistentes (14)(15) . O descarte e/ ou a limpeza adequada dessas vestimentas envolvem questões, no mínimo, de higiene básica dos trabalhadores ou de preocupação com a transmissão por contato, até que sejam lavados.…”
Section: Resultados E Discussão Dos Dadosunclassified
“…In relation to this issue, it was observed that 62 (89%) of the professionals working in Audiology use lab coat as protective equipment. The use of safety practices like this significantly reduces the risk of occupational injury 4 , and should be done independently of the use of write clothes or uniform, since it is a physical protection barrier for personal clothes 16 . In this research, only six professionals (8%) leave the PPE in the workplace, including lab coat.…”
Section: Discussionmentioning
confidence: 99%
“…The health care professionals are responsible for preventions and control of diseases and health promotion. However, they are not always aware of the importance of adopting biosecurity measures and ready to following the required steps in order to eliminate and/or reduce the risks for patients, themselves and for your staff 4 , which increases the chance of accidents and infections risks.…”
Section: Medidas De Biossegurança Adotadas Por Profissionais Atuantesmentioning
confidence: 99%
“…Marcela do Amaral de Albuquerque (1) , Valéria da Rocha Silveira Bernardo (2) , Luciana de Ornellas Silva (3) , Leila Coelho Nagib (4) , Silvana Frota (5) (1) Speech Therapist; Professional training at the Hospital Universitário Pedro Ernesto, Rio de Janeiro, RJ; Specialization in Clinical Occupational and Audiology. (2) Speech Therapist;Partner owns the Clinic Occupational Audiomed, Rio de Janeiro, RJ; Specialization in Clinical Occupational and Audiology.…”
Section: Biossegurança Em Fonoaudiologiamentioning
confidence: 99%
“…The manual defines Biosecurity, as the set of actions geared towards the prevention, minimization or elimination of health risks of professionals, its customers and the environment 1 . As well as in one of the studies of literature, the document also addresses items such as immunization of health professionals hand hygiene, the use of individual protection equipment, surfaces processing, processing of articles, among others 1,2 . In Brazil, biosecurity is regulated by Law Nº 11.105, of March 25, 2005, which provides for the National Biosafety Policy.…”
Section: Biossegurança Em Fonoaudiologiamentioning
confidence: 99%